Pengaruh Strategi Pemasaran dan Produk yang Ditawarkan dalam Upaya Menarik Minat Nasabah pada PT. Pegadaian - Wati, Sri Delima; Hidayat, Rahmat (Program Pascasarjana STIE Amkop Makassar, 2024)
This research aims to determine the influence of marketing strategies and products offered in attracting customers' buying interest at PT Pegadaian Binjai Branch. The research method used is a quantitative method. Quantitative research methods are effective tools for gaining valuable insights about populations and supporting decision making. This type of research involves collecting quantitative data from the entire population in the form of numbers, as well as applying statistical analysis techniques. The population of this research is the number of customers during the last 3 months, namely March - May 2024, totaling 95 customers. This research was carried out using multiple regression analysis methods, validity and reliability tests, hypothesis testing using statistical methods where data processing was carried out using the SPSS software program. The results of this research indicate that partially marketing strategies have a positive effect on purchase interest and products have a positive effect on purchase interest. Marketing strategy and products simultaneously influence purchasing interest.